Exercise improves subchondral bone microenvironment through regulating bone-cartilage crosstalk - Zhang, Shihua; Li, Tingting; Feng, Yao; Zhang, Keping; Zou, Jun; Weng, Xiquan; Yuan, Yu; Zhang, Lan (Frontiers in Endocrinology, 2023)
Articular cartilage degeneration has been proved to cause a variety of joint diseases, among which osteoarthritis is the most typical. Osteoarthritis is characterized by articular cartilage degeneration and persistent pain, which affects the quality of life of patients as well as brings a heavy burden to society. The occurrence and development of osteoarthritis is related to the disorder of the subchondral bone microenvironment. Appropriate exercise can improve the subchondral bone microenvironment, thus playing an essential role in preventing and treating osteoarthritis. However, the exact mechanism whereby exercise improves the subchondral bone microenvironment remains unclear. There is biomechanical interaction as well as biochemical crosstalk between bone and cartilage. And the crosstalk between bone and cartilage is the key to bone-cartilage homeostasis maintenance. From the perspective of biomechanical and biochemical crosstalk between bone and cartilage, this paper reviews the effects of exercise-mediated bone-cartilage crosstalk on the subchondral bone microenvironment, aiming to provide a theoretical basis for the prevention and treatment of degenerative bone diseases.